The comparative value of Greenleaf sudangrass and common sudangrass as pasture for fattening spring pigs. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
This experiment in the summer of 1954 used spring pigs on pasture. It was to compare the quality of the two varieties of sudangrass. Two lots were fed shelled corn and a mixed animal and plant protein supplement composed of 5 parts tankage, 4 parts soybean meal, and 1 part cottonseed meal. Both were self-fed, free choice. Lot 1 was pastured on Greenleaf sudangrass; Lot 2, on Common sudangrass. The pastures were the same quality and stand. Both furnished ample green forage throughout the test. It was necessary to clip the pastures during the summer to get rid of headed-out stalks and provide good, leafy forage. Both stood the dry weather equally well and were relished equally by the pigs, as well as could be determined by observations.
Keywords: Swine; Greenleaf sudangrass; Common sudangrass; Fattening pigs